2016
DOI: 10.1093/mnras/stw3329
|View full text |Cite
|
Sign up to set email alerts
|

Physical properties and astrometry of radio-emitting brown dwarf TVLM 513-46546 revisited

Abstract: We present multi-epoch astrometric observations of the M9 ultra-cool dwarf TVLM 513-46546 that is placed at the brown dwarf boundary. The new observations have been performed with the European VLBI Network (EVN) at 6 cm band. The target has been detected at 7 epochs spanning three years, with measured quiescent emission flux in the range 180 − 300 µJy. We identified four short-duration flaring events (0.5 − 2 mJy) with very high circular polarization (∼ 75% -100%). Properties of the observed radio flares suppo… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

1
2
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(3 citation statements)
references
References 43 publications
1
2
0
Order By: Relevance
“…Finally, observations spanning 10 yr confirmed that the quiescent emission can be temporally stable (e.g. Hallinan et al 2006;Gawroński, Goździewski & Katarzyński 2017), though we note two exceptions in the existing literature where the L2.5 dwarf 2MASS J05233822−1403022 (Berger 2006;Antonova et al 2007;Berger et al 2010) and the M9.5 dwarf BRI 0021 (Berger et al 2010) show long term variability in the quiescent emission at C-band frequencies.…”
Section: O B S E Rvat I O N Ssupporting
confidence: 72%
“…Finally, observations spanning 10 yr confirmed that the quiescent emission can be temporally stable (e.g. Hallinan et al 2006;Gawroński, Goździewski & Katarzyński 2017), though we note two exceptions in the existing literature where the L2.5 dwarf 2MASS J05233822−1403022 (Berger 2006;Antonova et al 2007;Berger et al 2010) and the M9.5 dwarf BRI 0021 (Berger et al 2010) show long term variability in the quiescent emission at C-band frequencies.…”
Section: O B S E Rvat I O N Ssupporting
confidence: 72%
“…Note that some objects have multiple observations in the same bandpass with both a detection and non-detection of O/IR variability. However, we do not expect the stability of O/IR variability to significantly impact the presence of quiescent radio emission, which observations confirm can persist for at least 10 yr (e.g., Hallinan et al 2006;Gawroński et al 2017), since the underlying driving mechanisms are different. In cases where data was re-examined, we defer to the updated results.…”
Section: Occurrence Rates Of Quiescent Radio Activitymentioning
confidence: 59%
“…We optimized the astrometric model with the same approach as presented in Gawroński et al (2017). Uncertainties of the model parameters ξ ξ ξ = (α 0 , δ 0 , µ α , µ δ , π) depend on complex way on the residual phase in phase-referencing, sub-mas changes of the phase calibrator radio structures and the atmospheric zenith delay residuals.…”
Section: Astrometric Model and An Estimate Of The Absolute Parallaxmentioning
confidence: 99%